Habermas and the Public Sphere: From a German to a European Perspective - Kleinsteuber, Hans J. (Javnost-The Public, 2001)
This article examines the nature and relevance of Habermas' theory of the public sphere in the present European situation. The paper notes that the current debate in the English-speaking world is not matched by a similar discussion in Germany. This is partly because Habermas' classic text was first published in Germany in 1962, and the considerable discussion it provoked ran out of steam some years ago. The Anglo-Saxon debate differs from its German predecessor in two important ways. In the first place, the choice of the phrase public sphere as a translation for the original Öffentlichkeit introduced issues into the English discussion, notably the spatial metaphor, that were absent from the German original. Secondly, in the German-speaking world there has been a much longer and broader discussion of Öffentlichkeit, lasting for more than a century, and concentrating particularly on literary and aesthetic issues. Very far from appearing as a startlingly original insight, as it did in the English-speaking world, Habermas' work was understood in Germany as a small part of this more general tradition.